AN ANALYSIS OF ARCS MODEL IN ENGLISH AS A FOREIGN LANGUAGE - Nanda Sari; Desi Sri Astuti; Sahrawi Sahrawi (XXXX-XXXX, 2021)
This research aimed to explore the implementation of ARCS Model in English as a Foreign Language that have done by the teacher and students at the eleventh grade of science students of SMA Muhammadiyah Sambas.  The research implemented a descriptive research design in qualitative method. There were 1 English teacher and 15 eleventh grade of science students participated in collecting primary data. The proposed research applied direct and indirect communication technique where utilized such tool as interview and online questionnaire (open-ended) which each consist of 10 questions. The questionnaire items were modified from Mahmudah (2016). This study used technique of analyzing the qualitative data from Ary, et al. (2010: 481). The research finding indicated that from interview, it was found that in implementing the model, in attention teacher using a variety of learning media such song, video, games and others interesting media. Teacher also use humor if it was needed. In showing relevance, teacher tried to show the relevance of the material being studied with students' needs and the benefits of learning English. Next, in improving students' confidence with their ability, teacher gave hope of success, arrange the learning process and give constructive feedback. Last in creating students' satisfied, teacher gave appreciation with verbal or non-verbal praise, provided an opportunity to showing their ability, and an opportunity to the students to help their friends. Furthermore, the research finding from questionnaire indicated that the use of ARCS Model motivational learning like humor, give the real examples, give feedback, and use praise make the students are easier to understand the lesson. It also makes students feel more motivated, comfortable, and compatible in learning. Thus, it allows the students to have full concentration on the lesson which leads to their motivationally of the learning. So students perceived ARCS Model is very useful model in creating and maintaining good interest among students that proved by students’ statement.